Formulating an Oil and Gas Revenue Sharing Fund Based on Rights Based Approach - Hadna, Agus Heruanto (UI Scholars Hub, 2017)
The backdrop to this research is the existence of dissatisfaction that has become pervasive among many local governments, producers of oil and gas in Indonesia, towards unjust oil and gas Revenue Sharing Fund (DBH) between central and local governments. To that end, the main objective of this research is to formulate a Revenue Sharing Fund of oil and gas production that is just for all parties by using a Rights-Based Approach (RBA). To provide the basis for the formula, the study uses qualitative method and the data collection techniques are in-depth interviews, FGD, and document analysis (desk study). The findings recommend two scenarios. The first scenario posits indigenous communities under two possibilities, i.e. either conferring share ownership in oil and gas business or the right to lease land in areas where oil and gas production occurs. The second scenario is to calculate oil and gas revenue sharing fund on the basis of governmental tier in a just and proportional manner, starting from the provincial, district, sub-district, village, and kampong levels, particularly for native and indigenous communities who are producers and non-producers of oil and gas.